Clinical manifestations and Nursing interventions in acute kidney injury in intensive care: an integrative review (Research, Society and Development, 2020)
This study aims to describe, according to the literature, the clinical manifestations of Acute Kidney Injury in patients hospitalized in Intensive Care Units and the main nursing interventions. This is an integrative review carried out on the databases: BDENF, LILACS, MEDLINE, PUBMED, SCIELO, SCOPUS and Web of Science, with a time cut from 2010 to 2020. As a result of the researches, 264 publications were found, of which 10 articles were included in the review according to the established eligibility criteria. Subsequently, the clinical manifestations identified in the studies were correlated by categories with the body systems affected by these. Thus, it can be evidenced that patients with Acute Kidney Injury can manifest several signs and symptoms originating both from the pathophysiological changes and from the therapeutic approaches selected for their treatment. In relation to nursing interventions, it was noted that these were directed, mainly for monitoring and control of blood volume and hydroelectrolytic disorders secondary to the condition. In addition, the extent and relevance of nurses' performance in the process of early identification, prevention and treatment of patients with Acute Kidney Injury admitted to Intensive Care Units has become known.